Evaluation of DVB-T2 transmission channel in Bangkok, Thailand - Suwansukho, Nattapan; Promwong, Sathaporn; Chamchoy, Monchai (My University, 2017)
This paper describes the evaluation of DVB-T2 transmission channel in Bangkok Thailand. The DVB-T2 test signal is transmitted in Bangkok Thailand. Type of transmission channel were used including Gaussian, Rician for fix rooftop reception. The measurements are consisting of a several environments such as open area, urban area, high building area. The measurement result are include Power Output from transmitter after combiner, LBER, bBER, NsMAR (Noise Margin), MER (Modulation Error Ratio), SNR (Signal to Noise Ratio), CNR (Carrier to Noise Ratio), and Signal. The measurement result of this paper lead to the evaluation of DVB-T2 transmission channel for environment of Bangkok, Thailand and could be useful to improve and to design the digital television broadcasting network in Thailand especially in urban area like Bangkok.
Keywords: DVB-T2; DVB-T2 Channel; DVB-T2 in Thailand; DVB-T2 Measurement; DVB-T2 Transmission